Peran Ibu Rumah Tangga Dalam Manajemen Keuangan Keluarga Selama Masa Pandemi Covid-19 - Febrian, Raden Aryo (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
The COVID-19 pandemic that has hit almost all parts of the world to date has caused instability in various sectors, especially in the economic sector. Economic instability that is felt in people's lives and has an impact on household life. Family income accompanied by increasing needs causes most households to experience difficulties in managing their family finances. Therefore, the role of housewives is needed in managing family finances properly and correctly during the COVID-19 pandemic to be able to maintain family welfare. The method used in this research is literature review. Literature review is research conducted by finding sources of information regarding theories related to the problems found. This study aims to describe the role of housewives in family management during the Covid-19 pandemic. The results of this study indicate that 1) a strategy that housewives can do in managing family finances well during the covid 19 pandemic is by implementing several steps, including determining the priority scale in meeting needs, making financial planning to distinguish between needs and wants. , make an ideal spending budget, make savings by shopping when shopping and calculate daily expenses by making daily and monthly shopping records, be wise in taking debts, and do something that can generate income such as a small business. 2) the efforts made by housewives to increase family income during the COVID-19 pandemic were carried out in various ways, such as opening a business in the food sector by processing food into various side dishes. Other efforts made by housewives to increase income families work odd jobs, grow crops, and others, as well as trade or do business online.